Pengaruh Konsentrasi Carboxyl Methyl Cellulosa (CMC) Terhadap Karakteristik Bubuk Daun Singkong (Manihot esculenta Crantz) Dengan Metode Foam Mat Drying - Intariani, Ni Putu; Diah Puspawati, Gusti Ayu Kadek; Wisaniyasa, Ni Wayan (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 11 No 4 (2022): Jurnal ITEPADO - 10.24843/itepa.2022.v11.i04.p14, 2022)
The cassava leaves ( Manihot esculenta Crantz ) is a type of green vegetable that contains nutrients and contains chlorophyll and flavonoids which are good for consumption, but the utilization of cassava leaves is still minimal and food diversification is needed. This study aimed to determine the concentration effect of CMC toward characteristics of cassava leaf powder with foam mat drying method and determine the appropriate concentration of CMC to produce cassava leaf powder with the best characteristics by foam mat drying method. The research used a completely randomized design (CRD) with CMC concentration treatment consisting of seven levels (0%, 0.5%, 1.0%, 1.5%, 2.0%, 2.5%, and 3.0%). The treatment was repeated twice, so that 14 experimental units were obtained. The data obtained were analyzed of variance and if the treatment had an effect on the observed parameters, it was continued with Duncan's Multiple Range Test (DMRT). The results showed that the concentration of CMC had a significant effect (P<0.05) on the observed parameters, namely water content, ash content, yield, total chlorophyll, flavonoid content, solubility, soluble time, and L*, a*, b* values. The best treatment was obtained at 3.0% CMC concentration with the following characteristics: water content of 1.53%, ash content of 5.77%, yield of 11.09%, total chlorophyll of 9.29 mg/g, flavonoid content of 11.39 mg QE/g, solubility of 82.82%, dissolving time of 28.85 s, L* value of 13.45, a* value of -36.15, and b* value of 10.55.